Paddy straw: an economical substrate for oyster mushroom (Pleurotus ostreatus) cultivation - Thomas Anne Sahithi Somavarapu; Arivu Sona; Shanmugam Vinodhini; Gundupalli Marttin Paulraj; Amornraksa Suksun (E3S Web of Conferences, 2022)
Cultivation of the Pleurotus ostreatus, oyster mushroom on paddy straw without supplements was investigated to follow circular economy concept to convert agricultural waste to value added products. Substrate nutrients, mushroom yield, and biological efficiency were determined. Three different extracts were used in this study (methanol, ethyl acetate, and hexane). Antioxidant and scavenging activity was determined using DPPH and H2O2. To find the essential compounds present in the mushrooms, GC-MS was analyzed. It was found that mushroom growth on paddy substrate was less than five days with excess mushroom yield. The biological efficiency was found between 54.5-130.9%, with the moisture of 93%. It was found that C, P, N, and K were integrated into mushrooms with these elements than in the utilized substrate. In DPPH results, the minimum concentration was 37.07 μg/ml, and the maximum was 67.2 μg/ml. IC50 value of 42.6 μg/ml were 50% for inhibition concentration. In H2O2, the minimum concentration was found to be 72.57 μg/ml, and the maximum was 98.02 μg/ml. This concentration indicates that the IC50 value of 84.07 μg/ml can be used in the biological process or component by 50% for inhibition concentration. The compounds include Oxirane, 2-Methyl-3-(1-Methylethyl)-, O-Methylisourea Hydrogen Sulfate, Diethyl Phthalate, 1,1,3,3-Tetrapropoxy- were found commonly in all three extracts. Hence, analysis of mushroom extracts is needed to determine the mechanisms of action of the various components for antimicrobial activity and inhibitory activity. Therefore, paddy straw could be used as an effective and economical substrate for oyster mushroom cultivation.